A rare homozygous variant of the NKX6-2 gene in association with profound intellectual disability - Lan, Hoang Thi Ngoc; Mai, Nguyen Phuong; Phuong, Doan Thi Kim; Lan, Hoang Thu; Ngoc, Nguyen Thi Minh; Lan Anh, Luong Thi (Tạp chí Nghiên cứu Y học, 2025)
This is a study of five children with profound intellectual disability, spastic quadriplegia, and nystagmus in two distinct families. Whole exome sequencing (WES) identified a homozygous c.234dup variant in the NKX6-2 gene relating to Spastic ataxia 8 with hypomyelinating leukodystrophy - the underlying cause of severe neurodevelopmental impairment in both families. The study contributed additional data on NKX6-2 variants in Vietnamese patients with intellectual disabilities and explored the genotype-phenotype correlation. Furthermore, it emphasized the importance of early genetic testing in children presenting with developmental delay, spastic quadriplegia, and unexplained nystagmus, especially when brain MRI findings suggested hypomyelinating leukodystrophy. This approach will provide a critical basis for diagnosis, patient management, and genetic counseling.